Explaining Brexit North and South of the Border. Issue 4 (November 2017) - McCrone, David
Abstract : The Brexit referendum in 2016 was a major turning-point in British and Scottish politics, reflected in a majority for Leave in England, but for Remain in Scotland. This article uses the British and Scottish Social Surveys for 2016 to explain Scottish-English differences, and finds that there were broad similarities in terms of social and demographic characteristics, and in terms of social values ('authoritarians' voting for Leave ). Being 'English', however, was much more significant than being 'Scottish' in accounting for Brexit vote. The association between Brexit vote and constitutional preferences, notably voting intention in a future Scottish Independence Referendum, is far less clear-cut. Brexit promises to be a political game-changer, but in ways which are complex and unpredictable.